Zooplankton abundance and biomass in Sørfjorden, Norway, on G.O. Sars in December 2019 sampled with a Hydrobios Multinet Mammoth - Hauss, Helena (PANGAEA, 2023)
Vertically stratified samples were collected during the ICES Broadband Acoustics course Sørfjorden, Norway, on G.O. Sars in December 2019. The goal was to obtain mesozooplankton diversity and abundance date to compare with a hydracoustic dataset collected with a TS probe. The used Hydrobios Multinet Mammoth had a 1m2net opening, eight nets (#9 was in the surface and discarded) nets, 300µm mesh, oblique haul during darkness in the at 2kn. Scanned on Epson V750 flatbed scanner at 2400dpi, processed using Zooprocess and uploaded to https://ecotaxa.obs-vlfr.fr/prj/6145 Exported data were used to estimate individual biomass according to Lehette & Hernandez-Leon (2006) and aggregated to depth layers. Data: GOSars_examples.zip contains example images.
Keywords: fjords; Zooplankton abundance; Zooplankton biomass; ZooScan